Association of the load-velocity relationship variables with 2000-m rowing ergometer performance. Issue 5 (4th May 2023) - Pérez-Castilla, Alejandro; Quidel-Catrilelbún, Mauricio Elías Leandro; Rodríguez-Pérez, Manuel A.; García-Ramos, Amador
ABSTRACT: This study aimed to compare the maximal mechanical variables derived from the load-velocity (L-V) relationship and 2000-meter rowing ergometer performance between rowers of different age categories, and to identify the L-V relationship variables more closely related to 2000-meter rowing ergometer performance. Nineteen competitive rowers (15 males and four females) aged between 15 and 25 years were evaluated during the national 2000-meter rowing ergometer competition organised by the Chilean Rowing Federation. Thereafter, the L-V relationship variables (load-axis intercept [ L 0 ], velocity-axis intercept [ v 0 ], and area under the L-V relationship line [ A line ]) were determined on separate occasions during the squat jump and prone bench pull exercises. Rowers were classified according to their chronological age for comparative purposes (under 16 years [U16] vs. over 16 years [O16]). L 0 and A line were always higher for O16 than for U16 ( p  ≤ 0.046; ES range = 0.99–1.79), while v 0 was generally comparable for both age categories ( p  ≥ 0.038; ES range = 0.07–1.03). Furthermore, the O16 revealed a greater performance (i.e. shorter total time) during the 2000-meter rowing ergometer competition ( p  = 0.011; ES = −1.31). In general, significant correlations were obtained between rowing performance and the L-V relationship variables obtained during the squat jump ( r or ρ range = −0.294 to −0.922) and prone bench pull ( r or ρ range = −0.322 to −0.928). These results support the L-V relationship as a sensitive procedure to evaluate the maximal mechanical capacities of lower- and upper-body muscles in competitive rowers. Highlights The load-velocity relationship variables are sensitive enough to differentiate between rowers of different age categories (U16 vs. O16). The load-velocity variables are significantly associated with 2000-meter rowing ergometer performance (total time). This novel testing methodology can provide practitioners and coaches with a simpler and more precise alternative to comprehensively assess a rower's maximal neuromuscular profiles.